2012
DOI: 10.1186/1472-6882-12-253
|View full text |Cite
|
Sign up to set email alerts
|

Frankincense essential oil prepared from hydrodistillation of Boswellia sacra gum resins induces human pancreatic cancer cell death in cultures and in a xenograft murine model

Abstract: BackgroundRegardless of the availability of therapeutic options, the overall 5-year survival for patients diagnosed with pancreatic cancer remains less than 5%. Gum resins from Boswellia species, also known as frankincense, have been used as a major ingredient in Ayurvedic and Chinese medicine to treat a variety of health-related conditions. Both frankincense chemical extracts and essential oil prepared from Boswellia species gum resins exhibit anti-neoplastic activity, and have been investigated as potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 52 publications
(71 reference statements)
4
80
1
4
Order By: Relevance
“…As p21 is negative regulator of G 1 phase transition, increased expression of this protein by the action of patchouli alcohol is indicative of cell cycle inhibition [65]. Similar arresting of the G 1 transition has also been reported in different types of cancer in response to various other EOs [66, 67]. EOs of Curcuma wenyujin inhibit S/G 2 phase transition leading to cancer cell death [68].…”
Section: Mechanism Of Action Of Eosmentioning
confidence: 88%
“…As p21 is negative regulator of G 1 phase transition, increased expression of this protein by the action of patchouli alcohol is indicative of cell cycle inhibition [65]. Similar arresting of the G 1 transition has also been reported in different types of cancer in response to various other EOs [66, 67]. EOs of Curcuma wenyujin inhibit S/G 2 phase transition leading to cancer cell death [68].…”
Section: Mechanism Of Action Of Eosmentioning
confidence: 88%
“…Various clinical and experimental studies have shown the potential anti-cancer properties of Frankincense (13). In this study, we investigated the cytotoxic effects of Frankincense aqueous fraction on KB cells, a subgroup of Hela cells.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of hydrodistillate of B. sacra gum resins was reported in pancreatic cancer cells with caspase-dependent apoptotis and rapid activation of Akt and Erk1/2 as possible mechanism (Ni et al, 2012).…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%